Biochar-based agricultural soil management: An application-dependent strategy for contributing to carbon neutrality. (August 2022) - Song, Biao; Almatrafi, Eydhah; Tan, Xiaofei; Luo, Songhao; Xiong, Weiping; Zhou, Chengyun; Qin, Meng; Liu, Yang; Cheng, Min; Zeng, Guangming; Gong, Jilai
Abstract: Biochar has received increasing attention in agricultural and environmental fields as an integrated solution to agricultural waste recycling, soil amendment, carbon sequestration, and greenhouse gas (GHG) reduction. However, obtaining the environmental benefits of biochar is limited by an inadequate number of soil applications. Currently, the willingness to use biochar in soil management is relatively low, which results from the insufficient understanding and promotion of the roles of biochar in soil management and climate change mitigation. This review article presents biochar applications based on carbon-neutral strategies in agricultural soil systems. The primary roles of biochar in soil improvement and remediation are discussed and the main soil application methods are introduced. The focus of this article is on biochar-based soil management strategies for contributing to carbon neutrality. Carbon sequestration using biochar is an application-dependent strategy, as the key to obtaining this ecological benefit is to store biochar products in soil via effective agricultural management. This article offers insights into biochar-based soil management strategies and their contribution to carbon neutrality in agricultural soil systems, with recommendations for appropriate government involvement in promoting biochar-based soil management and for incorporating biochar into the carbon trading market. Highlights: The non-CO2 GHGs account for the majority of carbon emission via agricultural soil. Incorporating biochar into the global carbon trading market is recommended. Using biochar to help achieve carbon neutrality is an application-dependent strategy.